Efektivitas Bimbingan Konseling Anak Di Griya Abhipraya Tanon Bapas Surakarta - Muhammad Rizal Fathoni; Budi Priyatmono (Jurnal Pendidikan Sosial Dan Konseling, 2026)
The protection of children in conflict with the law requires a special approach that takes into account their psychological and developmental conditions. This study aims to explore the counseling guidance program at Griya Abhipraya Tanon, which is designed to assist children clients in improving behavior and emotions. Using qualitative methods through interviews, observations, and case studies, this study analyzed two clients, AF and RTP, who experienced behavioral changes after attending the program. Results showed that although both showed progress, there were significant differences in outcomes between the two. RTP was able to socialize back to school without stigma, while AF still faced problems with her family. Barriers faced included a lack of motivation from clients and limited human resources and facilities at Griya Abhipraya. This study highlights the importance of support from the social environment and family in the success of counseling programs. It is recommended that the quality of human resources be improved, counseling programs be implemented consistently, and support from the community and family be strengthened, so that children can return to society with better personalities and skills.